Characterization of Shabu (methamphetamine) sold in Iloilo City - Giner, Gretchen Bo-Peep Glomo (Miagao, Iloilo University of the Philippines in the Visayas, 2007)
Knowledge of impurities adulterants in methamphetamine is important since it can reveal information on the synthetic methods used to produce the drug. It may link samples to a common source dealer or ilicit laboratory and the result is essential to the development of theories and practices on drug related studies for concerned government agencies as well asprivate agencies. The aim of this study is to improve and develop an analytical method for characterizing methamphetamine being sold in the market as well as to determine the najor adulterant present in illegally prepared methamphetamine. A transparent crystallinesubstance which was suspected to be metamphetamine was isolated and purified by the acid-base extraction. Impurities were extracted with chloroform and the sample was analyzed to contain 5.06% + 0.006 metamphetamine. Major peaks were selected for comparison andsimilarity and/or dissimilarity between street sample and purified sample using Fourier Transform Infra Red analysis (FT-IR). Results indicate the presence of methamphetamine in the sample with ephedrie as the major adulternant. Furthermore, Gas Chromatography-Mass Spectroscopy (GC-MS) analysis is reported for the sample to contain methamphetamine as indicated by standard identifying peaks.
Special Problem (Master of Chemistry) -- Miagao, Iloilo : U.P. in the Visayas, April 2007.
Keywords: Shabu (Methamphetamine) -- Characterization